A Three-Dimensional Finite Element Model of the Transibial Residual Limb and Prosthetic Socket to Predict Skin Temperatures - Peery, J.T.; Klute, G.K.; Blevins, J.J.; Ledoux, W.R. (IEEE transactions on neural systems and rehabilitation engineering, 2006)
Amputees who wear prosthetic limbs often experience discomfort from blisters and sores due to mechanical insult; these skin conditions are exacerbated by elevated skin temperatures and excessive perspiration within the prosthetic socket. The goal of this study was to create a tool for developing new prostheses that accommodate varying thermal loads arising from everyday activities. A three-dimensional thermal model of a transtibial residual limb and prosthesis was constructed using the finite element (FE) method. Transverse computerized tomography (CT) scans were used to specify the geometry of the residual limb and socket. Thermal properties from the literature were assigned to both biological tissue and prosthetic socket elements. The purpose of this work was to create a model that would aid in testing the effect of new prosthesis designs on skin temperature. To validate its output, the model was used to predict the skin temperature distribution in a common prosthetic socket system (silicone liner, wool sock, and carbon fiber socket) at rest with no mechanical loading. Skin temperatures were generally elevated near muscle and decreased anteriorly and at the distal end. Experimental temperature measurements taken at the skin-prosthesis interface of five human subjects were used to validate the model. Data extracted from the thermal model at anterior, posterior, lateral, and medial locations were typically within one standard deviation of experimental results; the mean temperatures were within 0.3 degC for each section and were within 0.1 degC overall